Molecular, Cellular and Model Organism Approaches for Understanding the Basis of Neurological Disease - Robert J. Harvey (Frontiers Research Topics, 2017)
The advent of next-generation sequencing technologies has resulted in a remarkable increase our understanding of human and animal neurological disorders through the identification of disease causing or protective sequence variants. However, in many cases, robust disease models are required to understand how changes at the DNA, RNA or protein level affect neuronal and synaptic function, or key signalling pathways. In turn, these models may enable understanding of key disease processes and the identification of new targets for the medicines of the future. This e-book contains original research papers and reviews that highlight either the impact of next-generation sequencing in the understanding of neurological disorders, or utilise molecular, cellular, and whole-organism models to validate disease-causing or protective sequence variants.